2020
DOI: 10.1080/02772248.2020.1839074
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal and small-scale gold mining activities and mercury exposure in Gorontalo Utara Regency, Indonesia

Abstract: Small-scale gold mining activities and their mercury emissions in the Gorontalo Utara Regency of the Gorontalo Province, Sulawesi Island, Indonesia, have been studied. The mining occurs in many areas of this region, but especially in the three villages Hulawa, Ilangata and Ilangata Barat. Mining activities in the Hulawa village are the oldest (19th century) in the regency, whereas mining in the Ilangata village began just 15 years ago. The activity level changes rapidly from time to time depending on the fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…The ore is then physically loaded into sacks and hauled to the processing facilities, where the crushed ore (30-40 kg) is put into a trommel, a steel mill grinder, where the gold is extracted from the ore using water and decimeter-sized boulders and milled for 3-4 h until the material is fine enough to release the gold. Then, roughly 500 g of Hg is fed into the rotating trommel for approximately 30 min to complete the amalgamation [19], after which the material is discharged, separated, and washed with bare hands to separate the gold from the nonbinding Hg while keeping the sediment aside for a second use. The resulting amalgam is burned inside or outside dwellings and gold shops, which emits Hg vapor into the surrounding area.…”
Section: Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…The ore is then physically loaded into sacks and hauled to the processing facilities, where the crushed ore (30-40 kg) is put into a trommel, a steel mill grinder, where the gold is extracted from the ore using water and decimeter-sized boulders and milled for 3-4 h until the material is fine enough to release the gold. Then, roughly 500 g of Hg is fed into the rotating trommel for approximately 30 min to complete the amalgamation [19], after which the material is discharged, separated, and washed with bare hands to separate the gold from the nonbinding Hg while keeping the sediment aside for a second use. The resulting amalgam is burned inside or outside dwellings and gold shops, which emits Hg vapor into the surrounding area.…”
Section: Indonesiamentioning
confidence: 99%
“…Nevertheless, CN dissolves the remaining Hg in the tailings, which generates the mercury cyanide complexes, Hg(CN) (2+N) (-N) (aq) compound, and causes significantly greater aquatic biota pollution than the elemental Hg [21]. In rivers, the sediment is washed and panned by women and children, and the gold is extracted from the sediment using Hg [19]. In some areas, the muddy water that is tainted by Hg-contaminated tailings is released directly into the local waterways, which then drains into the rice paddy fields and fish ponds [12].…”
Section: Indonesiamentioning
confidence: 99%
“…They are also undergone decalcified, silicified, dolomitizes process. Several studies showed that Hg contamination in Sulawesi was related to gold mining and processing (Abbas et al, 2020;Arifin et al, 2020;Bose-O'Reilly et al, 2010a;Castilhos et al, 2006;Limbong et al, 2004;Filho et al, 2004;IPEN, 2013;Limbong et al, 2003;Lusantono and Hantari, 2020;Mallongi et al, 2014;Mallongi, 2014;Mallongi and Herawaty, 2015;Nakazawa et al, 2016). A study from Tao et al (2020) presented that there is an interaction between lithology factors and watershed to the accumulation of Hg in karst soil where local mining activities and the mechanical transport of pollutant in the watershed has a strong dependence to Hg accumulation.…”
Section: Hg and Pb Distribution In The Soilmentioning
confidence: 99%
“…Indonesia emits the second largest amount of mercury in the world [ 15 ]. ASGM operations have spread widely in various provinces in Indonesia.…”
Section: Asgm Operations In Indonesiamentioning
confidence: 99%
“…Similar to the literature examining other provinces, studies conducted in Gorontalo have pointed out adverse effects of ASGM on the environment and human health. Mining operations in Hulawa villages in Gorontalo Utara Regency date back to the 19th century, whereas mining operations in Ilangata villages began just 15 years ago [ 15 ]. Inhabitants living close to ASGM sites experience higher hair mercury contamination than those living in non-ASGM sites [ 21 ].…”
Section: Asgm Operations In Indonesiamentioning
confidence: 99%